2009
DOI: 10.1017/s0007114509993084
|View full text |Cite
|
Sign up to set email alerts
|

High-fat, sucrose diet impairs geometrical and mechanical properties of cortical bone in mice

Abstract: Exposure to diets high in fat and sucrose can induce hyperinsulinaemia, affect Ca and Mg metabolism, and alter bone mineralisation and mechanical properties. The present study assessed morphological and mechanical changes in a murine model exposed to a high-fat/sucrose (HFS) diet, as well as corresponding molecular and endocrine markers of bone turnover. Female C57BL/6 mice (aged 9 weeks) consumed either a low-fat, complex carbohydrate diet or an HFS diet for 10 weeks. At the end of the 10 weeks, serum was col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 50 publications
2
33
2
Order By: Relevance
“…Both cortical and trabecular bones appear to be affected by diet-induced obesity in rapidly growing rodents. Long-term diet-induced obesity reduces the thickness and cross-sectional area of the cortical shell of the femoral neck [40] and tibia [41], significantly reducing the structural properties (loads, energies, stiffness normalized to body weight) [40]. Data from studies of diet-induced obesity suggest that the reductions in structural properties appear due, in part, to changes in trabecular microarchitecture (i.e., increased porosity [42], decreased trabecular number, increased trabecular separation and reduced connectivity [39,43,44] and a shift in trabecular organization from plate-to rod-like, which is reduced in strength [39,45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both cortical and trabecular bones appear to be affected by diet-induced obesity in rapidly growing rodents. Long-term diet-induced obesity reduces the thickness and cross-sectional area of the cortical shell of the femoral neck [40] and tibia [41], significantly reducing the structural properties (loads, energies, stiffness normalized to body weight) [40]. Data from studies of diet-induced obesity suggest that the reductions in structural properties appear due, in part, to changes in trabecular microarchitecture (i.e., increased porosity [42], decreased trabecular number, increased trabecular separation and reduced connectivity [39,43,44] and a shift in trabecular organization from plate-to rod-like, which is reduced in strength [39,45].…”
Section: Discussionmentioning
confidence: 99%
“…Bone resorption appears to be increased with dietinduced obesity as evidenced by increased serum concentrations of the resorption markers TRAP5b [41,43] and CTX [4,39] and by increased RANKL [41]. In addition, osteoclastogenesis and osteoclast activity in vitro are increased in bone cells from obese animals compared with lean controls [39,41,43,44]. In addition, compared with controls, diabetic rats have reduced osteoblast function and rates of bone formation [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…To examine the mineralization of the MC3T3-E1 cells, the cells were seeded at 5×10 4 per well in 24-well plates with differentiation medium containing vehicle (DMSO) or bezafibrate (100 μmol/L). After 21 d, the formation of mineralizing plaques was visualized by Alizarin red staining.…”
Section: Assay Of Mineralizationmentioning
confidence: 99%
“…Hypercholesterolemia was reported to be associated with lower bone mineral density (BMD) [2,3] . An animal model study has also demonstrated some detrimental effects of dyslipidemia on bone metabolism [4] . Fibrate use, including bezafibrate, was associated with a reduced odds of vertebral fractures in men and women [5] .…”
Section: Introductionmentioning
confidence: 99%
“…[5,8,10] In contrast, a combined high-fat/sucrose diet impairs lumbar and femoral neck strength in rodents, likely a result of smaller bone cross-sectional area and/or reduced cortical bone area in comparison to a low-fat/complex carbohydrate diet. [37,51] Interestingly, we observed that the cortical bone compartments at the distal femur and femoral diaphysis of HF and HF/F animals exhibited increased Ct.Th and Ct.Ar/Tt.Ar and densitometric characteristics, although, these changes did not improve whole bone mechanical characteristics in comparison with Controls. Regardless, our findings indicate that HF feeding produced divergent effects in the cortical and cancellous bone compartments, a concept that has been proposed by others.…”
Section: Discussionmentioning
confidence: 78%